2005
DOI: 10.1088/0031-9155/50/19/005
|View full text |Cite
|
Sign up to set email alerts
|

Dual-contrast echo planar imaging with keyhole: application to dynamic contrast-enhanced perfusion studies

Abstract: A new EPI-based method is presented which features optimized sampling of k-space enabling the integrated acquisition of two gradient echo images. The first of these images is predominantly T 1 weighted and the second is T * 2 weighted. The new method combines echo sharing of sparsely acquired high spatial frequency components with the keyhole technique and half-Fourier image reconstruction. The feasibility of acquiring high spatial and temporal resolution in vivo images for perfusion mapping is demonstrated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The current sw-dual-GRE sequence sacrifices coverage. Single-slice techniques are not recommended for quantitative assessment (23). However, a more recent version of the technique exists (23) and allows the measurement of four slices.…”
Section: Introductionmentioning
confidence: 99%
“…The current sw-dual-GRE sequence sacrifices coverage. Single-slice techniques are not recommended for quantitative assessment (23). However, a more recent version of the technique exists (23) and allows the measurement of four slices.…”
Section: Introductionmentioning
confidence: 99%
“…As the three sampling schemes represent very generic modifications of EPI, the findings are applicable to other EPI‐based time series applications including dynamic contrast enhanced (DCE) MRI, ASL, angiography, for example , diffusion, myocardial perfusion or fMRI, for example . Note that similar trajectories as in the inplace ACS scenario have been presented without parallel imaging, in the context of keyhole acquisitions and with varying acquisition density (without undersampling in k y direction) . The generality of PEAK‐EPI further allows for direct combination with other available advanced imaging techniques, such as multiband excitation.…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that the acquisition of dual or multiechoes is beneficial for correcting T 1 leakage effects . The achievements of PEAK‐EPI in terms of echo train reduction can be further used as part of multiecho acquisitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, this work uses parallel imaging acceleration of EPI with Keyhole (EPIK) for the DSC-MRI acquisition. The EPIK method was proposed in previous works 4,5 and validated at 1.5T 6,7 and recently at 3 T. 8,9 In these previous works, it was shown that EPIK outperforms single-shot EPI in terms of imaging speed and robustness, with respect to geometric distortions, while maintaining comparable performance in tracking dynamically changing MR signals such as those in functional (f )MRI. 6,8,9 Simulations to assess the EPIK method were also performed and the results are given in those works.…”
mentioning
confidence: 99%